PERANCANGAN DISTRIBUSI AIR BERSIH METODE DEADEND SYSTEM DESA KADUELA MENGGUNAKAN APLIKASI EPANET 2.2 - Gusti Fachrezy, Alrestu; Sonawan, Hery; Tohasan, Achmad (Universitas Majalengka, 2024)
Water is an important need for all life on this earth. The need for clean water always increases in line with population growth, while the supply of clean water continues to decrease. This research was conducted in Bina Loka hamlet block 4, Kaduela Village, Kuningan Regency. The problem that occurs in Bina Loka block 4 hamlet is that it does not receive a clean water supply from the water source available in Kaduela village, namely Tegala Biru Cicerem. So far, residents have received water supplies for their daily needs from neighboring villages, but the quality of the water is not suitable for consumption because it is yellowish in color and residents often complain that using the water causes problems, one of which is itching and diarrhea when consumed. For this reason, clean water distribution planning was carried out in Bina Loka hamlet block 4 with a total of 6 residents' houses, with an average of 8 people in each house. The design was carried out using the dead end system method with the help of the epanet 2.2 application with the target of each house getting water pressure of 5 – 7 mH2O and a minimum flow rate of 8 lpm per house.